2007
DOI: 10.1099/ijs.0.64456-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas delhiensis sp. nov., from a fly ash dumping site of a thermal power plant

Abstract: A phenanthrene-and citronellol-degrading bacterium, strain RLD-1 T , was isolated from the fly ash dumping site of a thermal power plant in Delhi, India. The 16S rRNA gene sequence indicated that this strain belongs to the genus Pseudomonas; high levels of sequence similarity were found with respect to Pseudomonas citronellolis DSM 50332 T (98.9 %), Pseudomonas jinjuensis DSM 16612 T (97.6 %) and Pseudomonas nitroreducens DSM 14399 T (97.5 %). Phylogenetic analysis based on 16S rRNA gene sequences placed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 18 publications
1
46
0
Order By: Relevance
“…We have already characterized several novel bacterial species from stressed environments including fly ash dumping sites of thermal power plants in Delhi and Kanpur, India (Prakash & Lal, 2006;Prakash et al, 2007), oil-contaminated site, Panipat oil refinery, India (Gupta et al, 2008(Gupta et al, , 2009, and a hexachlorocyclohexane dumpsite, situated at Ummari village, Lucknow, India (Kumar et al, 2008(Kumar et al, , 2015Singh & Lal, 2009;Verma et al, 2009Verma et al, , 2015Sharma et al, 2010;Malhotra et al, 2012;Dwivedi et al, 2013;Singh et al, 2013Singh et al, , 2014Singh et al, , 2015Mahato et al, 2015). To further analyse the bacteria from the hexachlorocyclohexane dumpsite, samples were collected from the drainage system of a lindane-producing unit (Lucknow, Uttar Pradesh, India; 268 549 N 818 099 E).…”
mentioning
confidence: 99%
“…We have already characterized several novel bacterial species from stressed environments including fly ash dumping sites of thermal power plants in Delhi and Kanpur, India (Prakash & Lal, 2006;Prakash et al, 2007), oil-contaminated site, Panipat oil refinery, India (Gupta et al, 2008(Gupta et al, , 2009, and a hexachlorocyclohexane dumpsite, situated at Ummari village, Lucknow, India (Kumar et al, 2008(Kumar et al, , 2015Singh & Lal, 2009;Verma et al, 2009Verma et al, , 2015Sharma et al, 2010;Malhotra et al, 2012;Dwivedi et al, 2013;Singh et al, 2013Singh et al, , 2014Singh et al, , 2015Mahato et al, 2015). To further analyse the bacteria from the hexachlorocyclohexane dumpsite, samples were collected from the drainage system of a lindane-producing unit (Lucknow, Uttar Pradesh, India; 268 549 N 818 099 E).…”
mentioning
confidence: 99%
“…Strain IP-10 T was isolated after 7 days incubation at 28 u C by plating serially diluted soil samples on Luria-Bertani agar plates (10 g tryptone, 5 g yeast extract, 5 g NaCl, 1 g D-glucose, 15 g agar per litre) containing nystatin (30 mg ml 21 ) and streptomycin (200 mg ml 21 ), used to isolate HCH-degrading sphingomonads (Vanbroekhoven et al, 2004). 16S rRNA gene sequence analysis, fatty acid profiling and other phenotypic characteristics revealed that the new isolate belonged to the genus Flavobacterium but exhibited sufficient significant differences from other closely related members of the genus to be considered as representing a novel species.16S rRNA gene sequence analysis was carried out as described by Prakash et al (2007). Briefly, a single colony of strain IP-10 T was picked with a sterile toothpick, suspended in 50 ml of sterile deionized water and heated at 95 uC for 10 min.…”
mentioning
confidence: 99%
“…A number of pseudomonads are known to utilize a variety of xenobiotics as sources of carbon and energy (Kiyohara et al, 1992;Johnsen et al, 1996;Stolz et al, 2007) and are thus exploited for the bioremediation of such compounds (O'Mahony et al, 2006;Onaca et al, 2007). Owing to their success in the bioremediation of soils with oily sludge (Lal & Khanna, 1996;Mishra et al, 1999Mishra et al, , 2001Whyte et al, 2001), there have been quite a large number of attempts to isolate Pseudomonas from such sites (Bhattacharya et al, 2003;Prakash et al, 2007a).In an ongoing study, a bacterial strain (Esp-1 T ) was isolated from an oil refinery (Panipat, India) that degrades citronellol (an isoprenoid and a component of oily sludge). Taxonomic studies based on 16S rRNA gene sequence analysis, morphological and physiological analysis, DNA-DNA relatedness and fatty acid patterns indicate that strain Esp-1 T represents a novel species of the genus Pseudomonas, for which the name Pseudomonas panipatensis sp.…”
mentioning
confidence: 99%
“…Cytochrome oxidase activity was determined by Kovac's reagent. Citronellol degradation, nitrate reduction, urease activity, and hydrolysis of starch, aesculin, hypoxanthine, xanthine, casein, gelatin, and Tweens 20 and 80 were determined as described by Prakash et al (2007a). Degradation of phenanthrene, anthracene and naphthalene was determined according to the protocol described by Kiyohara et al (1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation